Analysis of Mandibular Premolars Root Canal Morphology Using Radiographic and Cross-Sectional Techniques in Malaysian Population - Kranthi Raja Kacharaju; Padmini Hari; Ang Yee; Jaron Ngo; Muhamad Fareez Ismail (Wolters Kluwer Medknow Publications, 2019)
Introduction: Aberrant root canal morphology of mandibular premolars has always been associated with high endodontic treatment failures. This study was conducted to assess the canal morphology of the mandibular premolars in the Malaysian population using periapical radiographs and cross-sections of the premolar teeth. Materials and Methods: One hundred extracted permanent mandibular premolars with intact apex were randomly collected from various clinics across Malaysia. Radiographs were taken both in mesiodistal (MD) and buccolingual (BL) views to examine the presence of a second canal and to evaluate the type of canal configuration. The roots were then stained and perpendicularly resected to the long axis at three levels (cervical, middle, and apical one third). Digital photographs were taken for each of the cross-section sample and analyzed according to the number and shape of canals. Results: It was found that 78% of the mandibular premolars had single canal in BL radiographic view and 65% in MD view. Seventy-one percent of the single-canal premolars were observed in all three cross-sectional views (1-1-1 configuration). Furthermore, 37% showed oval-shaped canals and 34% showed irregular-shaped canals mainly found at cervical one third; 20% of the teeth showed the canals to be rounded in shape, most prevalent at the apical one third. Two canals with isthmus were observed in 5% of the all cross-sectional views. Conclusion: The majority of mandibular premolars in Malaysian population have a single canal, and there are a few possibilities of two or more canals in these teeth.